ACCOUNTING INFORMATION SYSTEMS, AUDIT QUALITY, AND SDG REPORTING: THE MEDIATING ROLE OF SUSTAINABILITY DISCLOSURE AND THE MODERATING EFFECT OF GOVERNANCE - Raya Puspita Sari Hasibuan; Putri Syuhada; Indri Dithisari; Eli Safrida (Universitas Tulungagung, 2026)
This study examines the growing importance of integrating accounting information systems and audit quality in enhancing organizational transparency and accountability, particularly in the context of Sustainable Development Goals (SDGs) reporting. As sustainability reporting becomes a critical component of corporate disclosure, organizations are required to ensure that the information presented is both reliable and relevant. Therefore, this research aims to analyze the influence of accounting information systems and audit quality on SDG reporting, while investigating the mediating role of sustainability disclosure and the moderating effect of governance quality. This study adopts a quantitative research approach using survey data collected from professionals involved in accounting, auditing, and financial reporting functions. The data are analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both measurement and structural models. The findings indicate that accounting information systems and audit quality have significant positive effects on sustainability disclosure, which in turn significantly enhances SDG reporting. Additionally, sustainability disclosure is found to partially mediate the relationship between the independent variables and SDG reporting. Governance quality also plays a significant moderating role, strengthening the relationship between both accounting information systems and audit quality with SDG reporting. These results highlight the importance of integrating technological systems, audit practices, and governance mechanisms to improve sustainability reporting practices. The study contributes to the literature by providing an integrated framework that links accounting systems, audit quality, and SDG reporting, and offers practical implications for organizations aiming to improve transparency and sustainability performance.